Understanding intrusion detection systems : detecting attackers and incidents inside your hosts and networks - Messier, Ric (O'Reilly, 2016)
"An outsider might be inside your network and ready to release attack traffic. A disgruntled employee might be inside your system and ready to delete files. You're a systems or network admin and it's your job to prevent these types of malicious events. Where do you begin? A good start is knowing with some certainty that the attackers are even present and a good intrusion detection system will do just that. In this video, security expert Ric Messier explains why intrusion detection systems are necessary, what they do, how they work, where to find them, and how to implement them."--Resource description page.